Implementing the Independent Curriculum in Indonesian Language Learning: A Qualitative Case Study of Fourth-Grade Students in Bengkulu Primary School - Monalisa Arsely; Irwan Satria; Adi Saputra (JPI: Jurnal Pustaka Indonesia, 2024)
This study investigates the implementation of the Independent Curriculum in Bahasa Indonesia instruction for fourth-grade students at SD Negeri 20 Kota Bengkulu. Drawing on the urgent need to recover learning losses and adapt to post-pandemic educational reforms, the research employed a qualitative field-based design to capture teacher and school leader perspectives through classroom observations, semi-structured interviews, and documentation analysis. The results indicate that the curriculum was implemented through three main stages planning, classroom practice, and assessment supported by the Merdeka Belajar digital platform, collaborative teacher working groups, and strong teacher motivation, but challenged by limited experience and insufficient training in adapting to a new subject-based structure. The discussion situates these findings within broader literature, highlighting how teacher autonomy, professional collaboration, and digital resources facilitate reform, while underscoring the persistent challenges of readiness and capacity-building in Indonesian primary schools. This study contributes novelty by providing localized empirical evidence from Bengkulu, an underrepresented region, thereby expanding understanding of how national policies are enacted in diverse contexts. The findings imply that strengthening teacher professional development, enhancing collaborative learning communities, and tailoring digital resources are essential strategies for ensuring the success of curriculum reform and its translation into meaningful student learning outcomes.